Association of sleep duration in pregnancy with preterm birth in China: a cross-sectional survey - Jiang, Hui; Yu, Bin; Liu, Yuanyang; Gao, Hui; Song, Ruijuan; Tan, Siyue; Han, Shufen; Zuo, Hui (Frontiers in Pediatrics, 2025)
IntroductionOnly a few studies have reported the relationship between the sleep duration of pregnant women and preterm birth (PTB), and the findings are inconsistent. This study aimed to examine the association of maternal sleep duration in pregnancy with PTB in China.MethodsA cross-sectional survey. Sleep duration in pregnancy and PTB status were self-reported via a validated questionnaire. The association of sleep duration in pregnancy with PTB was examined by logistic regression models.ResultsThe overall prevalence of PTB was 16.6%. Compared to the women with total sleep duration in pregnancy of >8 h/day, those with sleep duration of 7–8 h/day (OR = 1.43; 95% CI: 1.20, 1.70) and <7 h/day (OR = 4.28; 95% CI: 3.06, 6.00) had higher odds of reporting PTB after adjustment for gender of baby, maternal age at delivery, educational level of mother, educational level of father, diabetes history, gestation diseases including gestational hyperglycemia, gestational hypertension, anemia during pregnancy and anxiety or depression during pregnancy, and pregnancy behaviors including smoking or passive smoking during pregnancy, alcohol drinking during pregnancy, prenatal education, exercise during pregnancy and folic acid supplementation daily during pregnancy. The risk associations were similar in subgroups stratified by sex, gestational hyperglycemia, anemia during pregnancy and status of folic acid supplementation.DiscussionSleep duration in pregnancy was inversely associated with PTB in China. Our novel findings suggest the importance of sufficient sleep in pregnant women for the prevention of PTB. Further studies are warranted to confirm and elucidate the observed association.